Lymphotropic Deunedeous Therapy In Complex Treatment Of Patients With Hemorrhagic Stroke - Eshonov Olim Shoyimkulovich (Academia One Publishing, 2024)
The effectiveness of lymphotropic decongestant therapy in patients with hemorrhagic stroke was studied. Based on the obtained clinical and laboratory data, comparatively the main and control groups, the effectiveness of lymphotropic decongestant therapy was revealed, which prevents the progression of cerebral edema in this category of patients
Keywords: cerebral edema; hemorrhagic stroke; lymphotropic therapy